2021
DOI: 10.1136/lupus-2020-000471
|View full text |Cite
|
Sign up to set email alerts
|

Quick Systemic Lupus Activity Questionnaire (Q-SLAQ): a simplified version of SLAQ for patient-reported disease activity

Abstract: ObjectivesMost indices of disease activity in SLE combine physicians’ assessments and laboratory tests. However, there is also a need to capture patients’ perspectives of disease activity. Consequently, we need new, preferably quick and easy instruments to collect this information, which can be very useful for online consultations and registry purposes. We compared patients’ assessments of SLE disease impact/activity, as reported by a shorter version of the Quick Systemic Lupus Activity Questionnaire (Q-SLAQ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Ideally patient-reported IMID activity would be supplemented with clinician-assessed measures; however, both patient preferences and COVID-19 pandemic travel restrictions impacted the feasibility of inperson clinical assessments for all participants. Self-reported disease activity/state measures correlate with clinical assessment measures 19 35–37. As expected for these IMIDs, our population was predominantly female; thus, we lack power to detect sex-based differences in our outcomes and there is uncertainty as to how they would reflect a male-predominant cohort.…”
Section: Discussionmentioning
confidence: 85%
“…Ideally patient-reported IMID activity would be supplemented with clinician-assessed measures; however, both patient preferences and COVID-19 pandemic travel restrictions impacted the feasibility of inperson clinical assessments for all participants. Self-reported disease activity/state measures correlate with clinical assessment measures 19 35–37. As expected for these IMIDs, our population was predominantly female; thus, we lack power to detect sex-based differences in our outcomes and there is uncertainty as to how they would reflect a male-predominant cohort.…”
Section: Discussionmentioning
confidence: 85%
“…Questions used may not have fully assessed the potential impact of disease burden. Further research may consider including clinician‐reported or patient‐reported SLE disease activity measures, such as the Systemic Lupus Activity Questionnaire ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patient reported activity of SLE is measured by Quick Systemic Lupus Assessment Questionnaire (Q-SLAQ) 51 (translated to Danish by first author, see the supplementary S6), VAS fatigue (0-10), and VAS of global disease (0-10) by subject.…”
Section: Other Sle Activity Markers Assessed By Subjectmentioning
confidence: 99%